Scaling Ecological Resilience - Falk, Donald A.; Watts, Adam C.; Thode, Andrea E. (Frontiers in Ecology and Evolution, 2019)
Rapid climate change and altered disturbance regimes represent increasing stressors to the stability of existing ecosystems. Resilience is a widely used framework for post-disturbance response, but resilient responses are emergent properties resulting from component processes of persistence, recovery and reorganization, with different mechanisms at work in each mode. We present a model of scaled resilience, which allows resilience to be decomposed across scales of space, time, and levels of biological organization. Using case examples of post-fire resilience in dry conifer forests of interior western North America, we illustrate the increased clarity gained by separating scale-dependent mechanisms of persistence, recovery, and reorganization. We conclude by describing how the scaled resilience framework can be applied in land and fire management by distinguishing relevant management actions before, during, and after wildfire.